Biomass-based flexible nanoscale carbon fibers: effects of chemical structure on energy storage properties. Issue 16 (12th April 2021) - Zheng, Hao; Cao, Qiping; Zhu, Mengni; Xu, Dang; Guo, Haoyu; Li, Yao; Zhou, Jinghui
Abstract : The preparation of flexible nano-scale carbon materials with good energy storage properties using biomass is a challenging task. Abstract : The preparation of flexible nano-scale carbon materials with good energy storage properties using biomass is a challenging task. Herein, we developed a simple and efficient strategy for preparing high-performance green nano-scale carbon fibrous materials (CFs). A fractionated process is performed to obtain lignin with different chemical structures, including active chemical groups, branched structure, molecular weight and molecular spatial conformation. The fractionated lignin is phosphatized and mixed with cellulose acetate as a precursor material to prepare green nano-scale CFs by electrospinning. This strategy completely gets rid of the dependence of petroleum-based polymer spinning aids and endows biomass-based carbon materials with complete fibrous morphologies, uniform diameter, large surface area, good flexibility and excellent energy storage properties. The specific capacitance of biomass-based CFs as three-electrode capacitance reaches 363.1 F g −1 . At a power density of 800 W kg −1, the biomass-based CF supercapacitor device delivers an energy density of 31.2 W h kg −1 . Furthermore, the biomass-based CFs exhibit great potential for flexible free-standing supercapacitor with capacitance retention of ∼98% after 10 000 cycles.